Voting as a Signaling Device - R. Emre Aytimur; Aristotelis Boukouras; Robert Schwager (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
In this paper, citizens vote in order to influence the election outcome and in order to signal their unobserved characteristics to others. The model is one of rational voting and generates the following predictions: (i) The paradox of not voting does not arise, because the benefi t of voting does not vanish with population size. (ii) Turnout in elections is positively related to the size of the local community and the importance of social interactions. (iii) Voting may exhibit bandwagon effects and small changes in the electoral incentives may generate large changes in turnout due to signaling effects. (iv) Signaling incentives increase the sensitivity of turnout to voting incentives in communities with low opportunity cost of social interaction, while the opposite is true for communities with high cost of social interaction. Therefore, the model predicts less volatile turnout for the latter type of communities.
Keywords: C70; D72; D80; 330; electoral incentives; signaling; voting